Research in hospitality management and accounting: a research synthesis and analysis of current literature and future challenges - Paiva, I. S.; Reis, P.; Lourenço, I. C. (Problems and Perspectives in Management, 2016)
This study characterizes the results of social-scientific, behavioral science, and managerial/accounting research on current management and accounting matters in the hotel industry published in the most prestigious scientific hospitality journals and identifies avenues for future research. Based on an analysis of a set of 55 articles published in the journals that make up the SCImago Journal and Coutry Rank, published between 2005 and 2015, it is concluded that there is a lack of research in the financial accounting group; additional research is required for the small hotel category, and it is the important to use comparative studies that are better able to capture the characteristics of the hospitality industry. Additionally, most of the empirical studies analyzed come from European countries and statistical methods are extensively used in all topic areas. Finally, some gaps are identified in the literature and indicated future research priorities.